Recycling Silicon Kerf Waste and Quartz Pot Scrap for Silicon Production Via Carbothermic Reduction - Ryningen, Birgit; Dimd, Berhane Darsene; Ganesan, Nagarajan Somi; Tetlie, Pål; Bragstad, Irene; Bellmann, Martin; Jensen, Roar; Sørvik, Arvid Inge; Krogstad, Torfinn (SiliconPV Conference Proceedings, 2025)
The rise in photovoltaic (PV) waste across all stages of the PV value chain has created a need for efficient recycling solutions to reintroduce these materials into use. In response, the EU project (ICARUS) is exploring several recycling routes for key waste streams, including silicon kerf, quartz (used crucibles and pot scrap), and graphite (furnace insulation), for silicon production. This paper presents the development of a carbothermic recycling route that uses waste crucibles, pot scrap, and kerf as raw materials for silicon production. Silicon was produced in a pilot-scale submerged arc furnace, and its purity was analyzed using ICP-MS to quantify trace impurities and overall purity. The results showed that the silicon that is produced from waste materials closely matches the characteristics of metallurgical-grade silicon. These findings demonstrate the technical feasibility of waste materials in silicon production, with significant implications for industrial practices, sustainability efforts, and future policies aimed at promoting circular economies in high-demand sectors like silicon production.